Complicating the happy cure: psychoanalysis and the ends of analysis - Wright, Colin (Routledge, 2017)
This chapter explores the relative sidelining of psychoanalysis in critical approaches to Happiness Studies thus far. It argues that this stems from an American strand of psychoanalysis known as ego-psychology which forms an unacknowledged element in the genealogy of Happiness Studies itself. However, the chapter focusses primarily on Jacques Lacan’s critical interventions into ego-psychology and his elaboration of a contrasting psychoanalytic theory and practice. It is claimed that Lacan’s criticisms of happiness as an ego-based therapeutic ideology, and his related suspicion of models of ‘cure’, constitute a crucial resource for critical approaches to Happiness Studies. Finally, it is argued that, to this end, psychoanalysis is best approached as a clinical practice involving a tact with the subjective demand for happiness, rather than as a social or cultural theory that supports a generalised critique of happiness as a neoliberal ideology but misses, thereby, the affective hold over intimacy and sociality contemporary happiness has.